2017
DOI: 10.1186/s12889-017-4691-z
|View full text |Cite
|
Sign up to set email alerts
|

Childhood obesity and adult cardiovascular disease risk factors: a systematic review with meta-analysis

Abstract: BackgroundOverweight and obesity is a major public health concern that includes associations with the development of cardiovascular disease (CVD) risk factors during childhood and adolescence as well as premature mortality in adults. Despite the high prevalence of childhood and adolescent obesity as well as adult CVD, individual studies as well as previous systematic reviews examining the relationship between childhood obesity and adult CVD have yielded conflicting results. The purpose of this study was to use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
305
1
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 400 publications
(336 citation statements)
references
References 84 publications
(259 reference statements)
4
305
1
10
Order By: Relevance
“…There is considerable evidence to show that childhood obesity is a risk factor for type 2 diabetes, hypertension, coronary heart disease, and stroke in adulthood (hazard ratios ranging from 1.1 to 5.4) [33,34]. A systematic review of 23 studies reported that childhood obesity is significantly associated with adult systolic and diastolic blood pressure and triglycerides and inversely associated with high-density lipoprotein [35]. And hypertension is the leading cause of other noncommunicable diseases, such as high serum cholesterol, diabetes, etc.…”
Section: Long-term Health Impacts Of Malnutritionmentioning
confidence: 99%
“…There is considerable evidence to show that childhood obesity is a risk factor for type 2 diabetes, hypertension, coronary heart disease, and stroke in adulthood (hazard ratios ranging from 1.1 to 5.4) [33,34]. A systematic review of 23 studies reported that childhood obesity is significantly associated with adult systolic and diastolic blood pressure and triglycerides and inversely associated with high-density lipoprotein [35]. And hypertension is the leading cause of other noncommunicable diseases, such as high serum cholesterol, diabetes, etc.…”
Section: Long-term Health Impacts Of Malnutritionmentioning
confidence: 99%
“…This metric derives from the long-ago established observation that weight empirically scales as height squared, and has the advantage of being quickly and easily determined in clinical settings. Obtaining a detailed weight history from a patient can also yield important prognostic information, as the presence of overweight and obesity during childhood and adolescence has been suggested to confer increased CVD risk into adulthood [47]. Recent evidence suggests that historical maximum BMI is more strongly associated with mortality risk than single baseline BMI assessment [48].…”
Section: Assessment Of Adipositymentioning
confidence: 99%
“…Ожирение -это мультисистемное хроническое заболевание, имеющее разрушительные последствия для соматического и психоэмоционального состоя-ния организма, особенно в детском и подростковом возрасте [17]. Оно наиболее часто ассоциируется с сахарным диабетом 2-го типа, сердечно-сосудистой патологией, нарушениями функции репродуктив-ной и дыхательной систем, опорно-двигательного аппарата и желудочно-кишечного тракта [1,8,38]. В настоящее время в развитых странах частота встре-чаемости данного заболевания достигает 17 % среди детского и подросткового населения от 2 до 17 лет [22,28], стремительно увеличиваясь с возрастом.…”
Section: ожирение у подростков: психофизиологические аспекты патологииunclassified